2020
DOI: 10.1097/eja.0000000000001180
|View full text |Cite|
|
Sign up to set email alerts
|

European Society of Anaesthesiology guidelines on peri-operative use of ultrasound-guided for vascular access (PERSEUS vascular access)

Abstract: Ultrasound for diagnostic and procedural purposes is becoming a standard in daily clinical practice including anaesthesiology and peri-operative medicine. The project of European Society of Anaesthesiology (ESA) Task Force for the development of clinical guidelines on the PERioperative uSE of Ultra-Sound (PERSEUS) project has focused on the use of ultrasound in two areas that account for the majority of procedures performed routinely in the operating room: vascular access and regional anaesthesia. Given the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
224
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(236 citation statements)
references
References 168 publications
3
224
1
8
Order By: Relevance
“…Ultrasonographic assessment can be applied before, during, and after central venous cannulation, and provides clinicians with advantages of success, speed, and safety, by visualizing vessel viability, size, and patency, as well as the location of other adjacent anatomically important structures [12,33]. With respect to ultrasound-guided subclavian vein catheterization, although the quality of evidence is generally weak, the use of ultrasound-guidance is recommended in adult patients [9]. The results of the present study also provide supplemental evidence for the current guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonographic assessment can be applied before, during, and after central venous cannulation, and provides clinicians with advantages of success, speed, and safety, by visualizing vessel viability, size, and patency, as well as the location of other adjacent anatomically important structures [12,33]. With respect to ultrasound-guided subclavian vein catheterization, although the quality of evidence is generally weak, the use of ultrasound-guidance is recommended in adult patients [9]. The results of the present study also provide supplemental evidence for the current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasonography is widely used during vascular access in most medical facilities, and is recommended as a standard method during central venous catheterization by a number of professional organizations [ 9 11 ], a traditional landmark-based technique is still important and useful in certain clinical situation where the ultrasonography is not promptly available or when the operator is not familiar with the equipment. For anatomical landmark-based technique, although it is still uncertain how much increase in the cross-sectional area of the vein will affect the success of catheter placement, the cross-sectional area of the vein can theoretically have an impact on the success rate of venous catheterization by affecting the venipuncture success rate [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Several studies show that US guidance significantly reduces early mechanical complications, late infectious and thrombotic complications, the number of attempts and the costs not only for PICC and CICC, but also during FICC insertion. 1,34 In a recent guideline, a panel of experts have suggested that the benefits of US guidance documented in other studies for CFV might be extended to venous access to SFV. 1 This is very interesting from the clinical point of view, since the exit site of a non-tunneled FICC inserted in the SFV is located at mid-thigh, that is, far from the inguinal fold, in a clean, flat and stable area where dressings can be managed optimally, reducing the risk of infection and thrombosis.…”
Section: The Rafeva Protocolmentioning
confidence: 99%
“…1,34 In a recent guideline, a panel of experts have suggested that the benefits of US guidance documented in other studies for CFV might be extended to venous access to SFV. 1 This is very interesting from the clinical point of view, since the exit site of a non-tunneled FICC inserted in the SFV is located at mid-thigh, that is, far from the inguinal fold, in a clean, flat and stable area where dressings can be managed optimally, reducing the risk of infection and thrombosis.…”
Section: The Rafeva Protocolmentioning
confidence: 99%
See 1 more Smart Citation